ANALISIS ANALISIS PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), DAN EARNING PERSHARE (EPS) TERHADAP HARGA SAHAM (STUDI PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR FOOD AND BEVERAGES YANG TERDAFTAR DI BEI PERIODE 2018- 2021) - Vera Aprilianti; Diah Nurdiawaty; Linawati (Politeknik Kutaraja, 2023)
This study aims to analyze the effect of the current ratio (CR), debt to equity ratio (DER), and earnings per share (EPS) on stock prices in manufacturing companies in the food and beverages sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2018- 2021. The population in this study are all manufacturing companies in the food and beverages sub-sector that are listed on the IDX for the 2018-2021 period. The sample used is a food and beverage sub-sector manufacturing company listed on the IDX for the 2018-2021 period that meets the sample selection criteria. The data used is secondary data obtained from the financial reports of manufacturing companies in the food and beverages sub-sector listed on the IDX for the 2018-2021 period. The analysis used in this study is multiple linear regression using SPSS 25 software. The results show that simultaneously the current ratio (CR), debt to equity ratio (DER), and earnings per share (EPS) affect stock prices in manufacturing companies. the food and beverage sub-sector listed on the IDX for the 2018-2021 period. Partially the current ratio (CR) and earnings per share (EPS) have a positive effect on stock prices while the debt to equity ratio (DER) has a negative effect on stock prices in manufacturing companies in the food and beverages sub-sector listed on the IDX for the 2018-2021 period.